Practical Applications of Water Immersion Recovery Modalities for Team Sports. Issue 4 (August 2018) - Tavares, Francisco; Walker, Owen; Healey, Phil; Smith, Tiaki Brett; Driller, Matthew
Abstract : ABSTRACT: COLD THERAPIES ARE WIDELY USED MODALITIES TO ENHANCE RECOVERY WITHIN AN ATHLETIC POPULATION IN ADDITION TO OTHER ESSENTIAL COMPONENTS OF RECOVERY. ALTHOUGH THE BENEFITS OF COLD THERAPIES ARE DOCUMENTED IN THE SCIENTIFIC LITERATURE, RECENT RESEARCH HAS DEMONSTRATED SOME POTENTIAL HARMFUL EFFECTS OF SUCH MODALITIES AS WELL AS INDIVIDUAL RESPONSES TO SIMILAR PROTOCOLS. THIS ARTICLE REVIEWS THE CURRENT KNOWLEDGE ON THE DIFFERENT PROTOCOL CHARACTERISTICS AND INDIVIDUAL FACTORS THAT MAY CONTRIBUTE TO RESPONSES OF COLD THERAPIES, PROVIDING PRACTICAL RECOMMENDATIONS BASED ON EXTERNAL FACTORS, SUCH AS THE PHASE OF THE SEASON, THE DENSITY OF THE WEEKLY SCHEDULE, AND THE ATHLETES' GOALS.